(3MhGTj cGed GdeHQOs - (3gTGe Hf CMeO Hf gTGe GdcfGfj CHh GdhdjO, GdeYQha HGdnhnqbpTj , J (B489 (3g` s; (3eMeO Hf jRjO Hf YHO GdCcHQ GdKeGdj GdCROj, CHh GdYHGS, GdeYQha HGdeHQO,J (B286 (3g` s
(3ChdgG (B:s
(3CeG HYO MeO Gddg ceG jLH, hGdUdGI Ydi fHjg GdefJNH aEfj LeYJ aj gPG GdLRA eG CdajJg ef GdWQQ hGdMhGTj Ydi cJGH cGed, dCHj GdYHGS GdeHQO, hLYdJ YdGeI GdefShH Edjg (B((3Pdc(B) (3aj Chd cdGeg s
(3BNQgG (B:s
(3eHJhQ, hBNQ GdehLhO efgG(B: (3GdNhU(B: (3GdZGFQI GdYjhf, GdhGMO CNhU, hNhUGA, jQjO ef GdCYjGA s
(3fSNI KGfjIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B144 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B114s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B278 s
Keywords: (3GdCOHs